(untitled) (Research, Society and Development, 2025)
Mineral Trioxide Aggregate (MTA) has emerged as a material of choice in the treatment of root perforations, owing to its biocompatible properties and ability to promote the regeneration of selected tissues. Its field of use has been enhanced by new studies, research, and discussions. By investigating the efficacy of MTA and its alternatives in root perforations, the theoretical support is strengthened, thereby improving endodontic practices. The aim of this study was to analyze the use of MTA in the available literature concerning cases of root perforations. This research utilized a literature review across databases such as PubMed, Scielo, and Google Scholar, covering articles published between January 2014 and December 2024. MTA demonstrated high success rates in sealing root perforations, in addition to promoting proper placement and minimizing the risk of bacterial contamination. Its capacity to induce the formation of mineralized tissue and stimulate the reinforcement of periradicular tissues has been widely confirmed in clinical and experimental studies. MTA demonstrated excellent biocompatibility, as it reduces local inflammation and supports the recovery of the periodontium around the perforation area. Its use has also been effective in various types of perforations, whether small or large, in both conventional treatments and more complex situations, such as large perforations. Thus, it is concluded that the scientific literature reinforces the significance of MTA as an excellent material in the treatment of root perforations, contributing to the evolution of endodontic practices and the improvement of clinical outcomes.